Optimal MR Plaque Imaging for Cervical Carotid Artery Stenosis in Predicting the Development of Microembolic Signals during Exposure of Carotid Arteries in Endarterectomy: Comparison of 4 T1-Weighted Imaging Techniques - Sato, Y.; Ogasawara, K.; Narumi, S.; Sasaki, M.; Saito, A.; Tsushima, E.; Namba, T.; Kobayashi, M.; Yoshida, K.; Terayama, Y.; Ogawa, A. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: Preoperative identification of plaque vulnerability may allow improved risk stratification for patients considered for carotid endarterectomy. The present study aimed to determine which plaque imaging technique, cardiac-gated black-blood fast spin-echo, magnetization-prepared rapid acquisition of gradient echo, source image of 3D time-of-flight MR angiography, or noncardiac-gated spin-echo, most accurately predicts development of microembolic signals during exposure of carotid arteries in carotid endarterectomy.MATERIALS AND METHODS: Eighty patients with ICA stenosis (≥70%) underwent the 4 sequences of preoperative MR plaque imaging of the affected carotid bifurcation and then carotid endarterectomy under transcranial Doppler monitoring of microembolic signals in the ipsilateral middle cerebral artery. The contrast ratio of the carotid plaque was calculated by dividing plaque signal intensity by sternocleidomastoid muscle signal intensity.RESULTS: Microembolic signals during exposure of carotid arteries were detected in 23 patients (29%), 3 of whom developed new neurologic deficits postoperatively. Those deficits remained at 24 hours after surgery in only 1 patient. The area under the receiver operating characteristic curve to discriminate between the presence and absence of microembolic signals during exposure of the carotid arteries was significantly greater with nongated spin-echo than with black-blood fast spin-echo (difference between areas, 0.258; P < .0001), MPRAGE (difference between areas, 0.106; P = .0023), or source image of 3D time-of-flight MR angiography (difference between areas, 0.128; P = .0010). Negative binomial regression showed that in the 23 patients with microembolic signals, the contrast ratio was associated with the number of microembolic signals only in nongated spin-echo (risk ratio, 1.36; 95% confidence interval, 1.01–1.97; P < .001).CONCLUSIONS: Nongated spin-echo may predict the development of microembolic signals during exposure of the carotid arteries in carotid endarterectomy more accurately than other MR plaque imaging techniques.AUCarea under the receiver operating characteristic curveBB-FSEblack-blood fast spin-echoCEAcarotid endarterectomyCRcontrast ratioMESmicroembolic signalsROCreceiver operating characteristicSEspin-echoSI-MRAsource image of 3D time-of-flight MR angiographyTCDtranscranial Doppler